Effect of a Health Literacy for Fall Prevention Enhancing Program on Practices of Recurrent Fall Prevention Among the Elderly in Communities - Luehan, Supawan; Narin, Rangsiya; Sripetwandee, Noppamas (Nursing Journal CMU, 2024)
Health Literacy is an important outcome factor of elderly health behaviors; thus, enhancing health literacy is necessary. This quasi-experimental research study, with a two-group pretest-posttest design, aimed to study the effect of a program for enhancing health literacy for fall prevention on practices of recurrent fall prevention of the elderly in communities, developed from the health literacy concept by Don Nutbeam. The participants were 50 elderly persons who had a history of falling at least once per year, recruited using purposive sampling, and assigned to an experimental group (n = 25) or a control group (n = 25). The research instruments consisted of 1) an 8-week program for enhancing health literacy for fall prevention on practices of recurrent fall prevention; 2) media and a guidebook on health literacy for fall prevention; and 3) an interview questionnaire on the practices of recurrent fall prevention among the elderly in the community, which was examined for content validity by six experts, demonstrating a content validity index of .97 and a Cronbach's alpha coefficient of confidence of .75. Data were analyzed using descriptive statistics, paired sample t-test, and independent t-test. The results revealed that the experimental group had higher mean scores for practices of recurrent fall prevention (M = 31.00, SD = 1.15, p < 0.001) than before receiving the program (M = 22.20, SD = 5.19) and higher scores than those of the control group (M = 22.44, SD = 6.70), with statistical significance (p < 0.001). The results from this research revealed that community nurse practitioners and healthcare teams can apply the health literacy enhancement program as a guideline for promoting health literacy and effective practices in preventing recurrence of falls among the elderly in communities.